The Potential Role of Motor Unit Number Estimation as an Additional Diagnostic and Prognostic Value in Canine Neurology - Kauder, Julia; Petri, Susanne; Tipold, Andrea; Stein, Veronika M. (Frontiers in Veterinary Science, 2015)
Motor unit number estimation (MUNE) is an electrophysiological technique to assess the number of motor units innervating a single muscle or muscle group of interest. It may quantify axonal loss in any disease involving injury or degeneration of ventral horn cells or motor axons. Since MUNE has rarely been used in veterinary medicine, our study aimed to evaluate its potential role as an additional diagnostic and prognostic parameter in canine neurology. Therefore, we examined 5 healthy dogs and 7 dogs suffering from diseases that necessitated general anesthesia for further diagnostics and treatment and that were not expected to interfere with the results of electrodiagnostic testing. By using the incremental technique to study MUNE in the cranial tibial muscle, we determined the number of motor units, the size of the compound muscle action potential and the mean size of individual motor unit potentials of each dog as well as the mean values for each group. Moreover, we studied the correlation between these parameters. Taking the results into consideration, we addressed the difficulties and limitations of this technique. We, furthermore, pointed out possible fields of application for MUNE in canine neurology, and emphasized several aspects that future studies should focus on when applying MUNE to canine patients.